Determinants of Compliance With The Implementation of The Covid-19 Health Protocol In The Community of Kediri City - Sari, Dhita Kurnia; Fawzi, Alfian (Universitas STRADA Indonesia, 2021)
Background: The implementation of the Covid-19 disease prevention health protocol is still a problem in some areas. Many police officers found violations of the Covid-19 prevention health protocol. There are indications that the behavior of the Indonesian people is not ready to face the covid-19 outbreak, which is characterized by four types of behavior, one of which shows non-compliance.Purpose: This study aimed to examine what are the most dominant determinants of knowledge, anxiety, age, gender, and personality type in influencing compliance in implementing the COVID-19 health protocol.Methods: The population in this study is the entire community in the city of Kediri. By using accidental sampling method with a cross-sectional approach. And the sample obtained as many as 114 respondents.Results: The results of the research that have been carried out and analyzed show that the variables of knowledge, personality and anxiety affect health protocol compliance by 57.4% and the rest are influenced by other variables that have not been studied, and the most influencing variable in the study is the knowledge variable in the partial test.Conclusion: Compliance and awareness in the implementation of the covid 19 protocol, there is a need for cooperation from the government to the community so that the spread of covid 19 in Indonesia can be prevented